Pregunta
\( 2 x^{2}+x+3=0 \) The solution set is \( \} \). Use the quadratic formula to solve the equation. (Type an exact answer, using radicals as needed. Use a comma to separate answers as needed.)
Ask by Bond Bates. in the United States
Feb 04,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The solutions are \( x = \frac{-1 + i\sqrt{23}}{4} \) and \( x = \frac{-1 - i\sqrt{23}}{4} \).
Solución
To solve the quadratic equation \( 2x^{2} + x + 3 = 0 \) using the quadratic formula, follow these steps:
The quadratic formula is:
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
where \( a = 2 \), \( b = 1 \), and \( c = 3 \).
1. **Calculate the discriminant (\( \Delta \)):**
\[
\Delta = b^2 - 4ac = 1^2 - 4 \cdot 2 \cdot 3 = 1 - 24 = -23
\]
Since the discriminant is negative, the solutions will be complex numbers.
2. **Substitute the values into the formula:**
\[
x = \frac{-1 \pm \sqrt{-23}}{2 \cdot 2} = \frac{-1 \pm i\sqrt{23}}{4}
\]
where \( i \) is the imaginary unit.
3. **Write the solution set:**
\[
\left\{ \frac{-1 + i\sqrt{23}}{4}, \; \frac{-1 - i\sqrt{23}}{4} \right\}
\]
**Final Answer:**
\[
\left\{\, \dfrac{-1 + \sqrt{-23}}{4},\; \dfrac{-1 - \sqrt{-23}}{4} \,\right\}
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To solve the quadratic equation \( 2x^{2}+x+3=0 \) using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2-4ac}}{2a} \), we first identify the coefficients: \( a = 2 \), \( b = 1 \), and \( c = 3 \). Calculate the discriminant: \[ b^2 - 4ac = 1^2 - 4(2)(3) = 1 - 24 = -23 \] Since the discriminant is negative, the solutions will be complex. Now apply the quadratic formula: \[ x = \frac{-1 \pm \sqrt{-23}}{2(2)} = \frac{-1 \pm i\sqrt{23}}{4} \] Thus, the solution set is: \[ \left\{ \frac{-1 + i\sqrt{23}}{4}, \frac{-1 - i\sqrt{23}}{4} \right\} \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium